153 Supplementing an immunomodulatory feed ingredient to modulate thermoregulation and performance in finishing beef cattle under heat stress conditions. (29th July 2019) - Colombo, Eduardo; Cooke, Reinaldo F; Schubach, Kelsey; Rett, Bruna; Brandão, Alice
Abstract: This experiment compared body temperature and productive parameters in finishing cattle managed under heat stress conditions, and supplemented or not with a supplement based on yeast and B-complex vitamins (Omnigen-AF; OMN; Phibro Animal Health, Teaneck, NJ). Bos taurus × B. indicus cattle (64 heifers and 64 steers) were ranked by initial body weight (BW; 440 ± 3 kg) and sex, and allocated to 1 of 16 pens (8 heifers or steers/pen). Pens within sex were randomly assigned to receive (n = 8) or not (CON; n = 8) OMN at 56 g/cow daily (as-fed basis). Cattle received a total-mixed ration (d 0 to 106), and OMN was offered daily as a top-dress. Cattle were shipped on d 107 to a commercial packing facility (Friona, TX) for slaughter. Cattle BW was recorded on d 0, 14, 28, 42, 56, 70, 96, and 106. Feed intake was evaluated by measuring offer and refusals biweekly from each pen. Feed efficiency was calculated from each pen according to total feed intake and BW gain. From d 0 to 7, 28 to 42, and 84 to 98, heifer intravaginal temperature was recorded hourly (iButton temperature loggers DS1922L, Maxim Integrated, San Jose, CA). Environmental temperature humidity index (THI) was also recorded hourly throughout the experiment, and averaged 79.8 ± 0.6. Heifers receiving OMN had less (P ≤ 0.05) vaginal temperature from 1500 to 1900h across sampling days (39.05 vs. 39.19 °C, respectively; SEM = 0.04), when THI ranged from 85.3 to 90.1. However, no treatment effects were detected (P ≥ 0.20) for BW gain, feed intake, feed efficiency, and carcass traits upon slaughter (P ≥ 0.22). Collectively, results from this experiment suggest that OMN ameliorated hyperthermia in finishing cattle exposed to heat stress conditions, but such benefit was not sufficient to improve productive and carcass parameters